PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PEMERIKSAAN TANDA VITAL PROGRAM STUDI DIII KEPERAWATAN UNUSA - Chilyatiz Zahroh; Siti Muflihah (Universitas Nahdlatul Ulama Surabaya, 2015)
Development of video learning media examination of vital signs on Diploma 3 Nursing Programme in Unusa. Video is the media to help the implementation of practical learning independently. The utilization of video for DIII nursing program even UNUSA was minimum because there had never been research development related of action or competencies of nursing, particularly the examination of vital signs: blood pressure, temperature, pulse and breathing. The purpose of this research were to develop and to find out the feasibility of video learning media examination of vital signs. The methods used in this research was Research Development (Research & Development). The Model used was the development of procedural models, i.e. models that are descriptive, indicating the steps to be followed to produce a product. On the research of the development of this will result in a product video learning media examination of Vital Signs. Research conducted through the preliminary study stage, development and evaluation. The results showed that (1) the resulting video learning examination of Vital Signs, (2) media expert and video learning material stated examination of vital signs declared eligible. Video learning Media examination of vital signs can be used as a medium of learning alternative to increase motivation, independence and creativity of students in improving skills examination of vital signs. Educators also are expected to be motivated to make a video learning competence of the other as an alternative medium of learning.